2001
DOI: 10.1001/archderm.137.12.1627
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dermatologists' and Primary Care Physicians' Accuracy in Diagnosing Melanoma

Abstract: To compare the accuracy of dermatologists and primary care physicians (PCPs) in identifying pigmented lesions suggestive of melanoma and making the appropriate management decision to perform a biopsy or to refer the patient to a specialist.Data Sources: Studies published between January 1966 and October 1999 in the MEDLINE, EMBASE, and Can-cerLit databases; reference lists of identified studies; abstracts from recent conference proceedings; and direct contact with investigators. Medical subject headings includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 42 publications
1
59
1
2
Order By: Relevance
“…Although a systematic review has suggested that there is insufficient evidence to demonstrate differences in dermatologists' and primary care physicians' diagnostic accuracy of lesions suggestive of melanoma, 10 the current study suggests that melanomas excised in primary care were less likely to have been correctly diagnosed by the person performing the biopsy (19.5% versus 54.7%, P<0.001). Interestingly, a previous study from the same group found that basal cell carcinoma is both less likely to have an accurate diagnosis and less likely to be fully excised if this is done in primary care.…”
Section: What Does This Mean For Practice?contrasting
confidence: 66%
“…Although a systematic review has suggested that there is insufficient evidence to demonstrate differences in dermatologists' and primary care physicians' diagnostic accuracy of lesions suggestive of melanoma, 10 the current study suggests that melanomas excised in primary care were less likely to have been correctly diagnosed by the person performing the biopsy (19.5% versus 54.7%, P<0.001). Interestingly, a previous study from the same group found that basal cell carcinoma is both less likely to have an accurate diagnosis and less likely to be fully excised if this is done in primary care.…”
Section: What Does This Mean For Practice?contrasting
confidence: 66%
“…The USPSTF made this recommendation based on (1) the lack of quality evidence that links screening to improved health outcomes and (2) limited information about the ability of PCPs to perform adequate examinations in the context of usual care 18 . With regard to the latter, it has been suggested that PCPs may not be prepared or sufficiently trained to identify early skin cancer [18][19][20][21] . An effective training program is essential prior to conducting a rigorous screening trial designed to ultimately determine the efficacy of clinician skin examination and its impact on melanoma mortality reduction.…”
Section: Introductionmentioning
confidence: 99%
“…GPs are less accurate than dermatologists in the diagnosis of skin cancers, 4,5 and there is conflicting, 6,7 and probably insufficient, 8 evidence about the confidence and ability of GPs to manage pigmented skin lesions. GPs are able to improve their diagnostic and management skills in dermatology through a variety of training methods, 9 sometimes to the level of specialists.…”
Section: Introductionmentioning
confidence: 99%